GRECO ROMAN WRESTLING: HISTORICAL ROOTS, DEVELOPMENT, AND CONTEMPORARY SIGNIFICANCE - Xolmatov Azizjon Ibraximovich (Sciental Journals Publishing, 2025)
This article explores the origins, historical development, and modern-day significance of Greco-Roman wrestling. Tracing its roots back to ancient civilizations, the study highlights how the sport evolved through various eras and became a disciplined and respected form of athletic competition. Special attention is given to its role in international sports, particularly the Olympic Games, and its impact on physical education and cultural identity in different societies.
Keywords: Greco-Roman wrestling, history of wrestling, Olympic sports, ancient sports, wrestling development, traditional wrestling, modern wrestling, cultural heritage.